Society and Malay Culture to Face the Challenges of the Times - Warni, Warni; Karim, Maizar (Proceeding International Conference on Malay Identity, 2023)
Malay society and culture encompass the entire Malay nation and culture in the archipelago, peninsula, and mainland Southeast Asia. They are united by racial and ethnic group unity, language, primordial cultural patterns, religious beliefs, and similarities in fate and level of development. The Malay tribes are now geo-politically grouped into two parts: those with their own countries and those under the rule of non-Malay groups. In the first three regions, which have become independent states since World War II, the Malays are the dominant majority group. The Malay ethnic group has many cultural heritages, including the oldest literary heritage from the 7th to the 14th century and the younger heritage preserved in around 5000-10000 ancient manuscripts. Literature is the basis of the Malay cultural tradition, containing thoughts, feelings, customs, beliefs, religious teachings, history, law, philosophy, politics, literature, astronomy, moral teachings, education, mantras, prayers, medicines, mysticism, language, buildings, plants, and the value system of past societies. The Malay community is open to the times and has a stable life due to their traditions. They rely on a sense of community, patterned from the village system and common economic and safety needs. Abstrak Masyarakat dan budaya Melayu mencakup seluruh bangsa dan budaya Melayu di kepulauan, semenanjung, dan daratan Asia Tenggara. Mereka disatukan oleh kesatuan ras dan kelompok etnis, bahasa, pola budaya primordial, kepercayaan agama, dan kesamaan nasib dan tingkat perkembangan. Suku-suku Melayu sekarang secara geo-politik dikelompokkan menjadi dua bagian: mereka yang memiliki negara sendiri dan mereka yang berada di bawah kekuasaan kelompok-kelompok non-Melayu. Di tiga wilayah pertama, yang telah menjadi negara merdeka sejak Perang Dunia II, suku Melayu adalah kelompok mayoritas yang dominan. Kelompok etnis Melayu memiliki banyak warisan budaya, termasuk warisan sastra tertua dari abad ke-7 hingga abad ke-14 dan warisan yang lebih muda yang tersimpan dalam sekitar 5000-10000 naskah kuno. Sastra adalah dasar dari tradisi budaya Melayu, yang berisi pemikiran, perasaan, adat istiadat, kepercayaan, ajaran agama, sejarah, hukum, filsafat, politik, kesusasteraan, astronomi, ajaran moral, pendidikan, mantra, doa, obat-obatan, mistik, bahasa, bangunan, tanaman, dan sistem nilai masyarakat masa lalu. Masyarakat Melayu terbuka terhadap perkembangan zaman dan memiliki kehidupan yang stabil karena tradisi mereka. Mereka mengandalkan rasa kebersamaan, berpola dari sistem desa dan kebutuhan ekonomi dan keamanan bersama.